Chasing endless summer : [large type] a novel - Andrews, V. C. (Virginia C.) (Andrews, V. C. (Virginia C.). Sutherland series, 2024)
"After the tragic death of her mother and a long period of isolation under the thumb of a cruel grandfather, young Caroline Bryer has little to hope for in her life in the foreboding Sutherland mansion. Her only companion, her enigmatic cousin, Simon, may be a wolf in sheep's clothing and is not to be trusted. When Caroline's estranged father suddenly resurfaces in Hawaii with a new wife and stepchildren that she'll finally be allowed to visit, Caroline dares to hope for a new, normal life. Desperate for her father's love, Caroline will do anything to stay in this new home. But her troublesome stepsister has other plans, and Caroline cannot tell who to trust and who to run from. Will her new stepbrother and stepsister be a light in her dark life, or will they blot out the last slivers of sun forever?"--